Role of Environmental Dynamics in Moderating the Influence of Digital Leadership, Digital Transformation, and Digital Innovation on the Financial Performance of the Indonesian Energy Sector - Pujisari, Yusti; Vidyaningrum, Bunga; Susliyanti, Eni Dwi; Zahara, Inna (Amkop Management Accounting Review (AMAR), 2025)
The energy sector in Indonesia faces dual challenges of transitioning toward clean energy and digitizing business processes. This study examines the relationships among digital leadership, digital transformation, digital innovation, environmental dynamism, and financial performance. A quantitative approach using Partial Least Squares-Structural Equation Modeling (PLS-SEM) was applied to energy companies, complemented by qualitative data from focus group discussions (FGDs) and interviews. The findings reveal that digital innovation has a significant impact on financial performance, whereas digital leadership and digital transformation show no direct effects. Digital leadership acts as a strategic enabler by fostering transformation and innovation, but its financial impact is indirect. Mediation tests indicate that neither digital transformation nor digital innovation mediates the relationship between digital leadership and financial performance. Furthermore, environmental dynamism does not significantly moderate the relationships among the core variables, suggesting that financial outcomes are more strongly determined by internal factors than external pressures. Qualitative evidence supports this conclusion, highlighting that fluctuations in energy prices and regulatory changes exert limited influence, while internal drivers such as visionary leadership, technological readiness, and an innovation-oriented culture are more decisive. Theoretically, this study contributes to the literature on Dynamic Capabilities Theory and the Resource-Based View within the energy sector. Practically, the findings underscore the importance of strengthening digital leadership and embedding innovation into business strategy to enhance sustainable financial performance.